(untitled) (Revista Tempo e Argumento, 2016)
Between 1959 and 1977, there were more than 17 armed organizations in Argentina. Beyond the success achieved, all of them proposed a combination of armed struggle and popular mobilization. To do this, they tried to carry out the so-called “mass work.” Two of them, Montoneros and PRT-ERP, were very successful in “inserting” the organization among the population as a whole. Herein, the insertion of the second of these organizations is addressed, and we postulate that guerrilla as a theme, in Argentina, was much more complex than we assume. In fact, the relationship between guerrilla and popular organization proposes that armed struggle was the result of a historical process and social demands, and not merely a conjunctural fact.